A pH‐Triggered Polymer Degradation or Drug Delivery System by Light‐Mediated Cis/Trans Isomerization of o‐Hydroxy Cinnamates - Abramov, Alex; Maiti, Binoy; Keridou, Ina; Puiggalí, Jordi; Reiser, Oliver; Díaz, David Díaz (Macromolecular rapid communications., 2021)
A new methodology for the pH‐triggered degradation of polymers or for the release of drugs under visible light irradiation based on the cyclization of ortho‐hydroxy‐cinnamates (oHC) to coumarins is described. The key oHC structural motif can be readily incorporated into the rational design of novel photocleavable polymers via click chemistry. This main‐chain moiety undergoes a fast photocleavage when irradiated with 455 nm light provided that a suitable base is added. A series of polyethylene glycol‐alt‐ortho‐hydroxy cinnamate (polyethylene glycol (PEG)n‐alt‐oHC)‐based polymers are synthesized and the time‐dependent visible‐light initiated cleavage of the photoactive monomer and polymer is investigated in solution by a variety of spectroscopic and chromatographic techniques. The photo‐degradation behavior of the water‐soluble poly(PEG2000‐alt‐oHC) is investigated within a broad pH range (pH = 2.1–11.8), demonstrating fast degradation at pH 11.8, while the stability of the polymer is greatly enhanced at pH 2.1. Moreover, the neat polymer shows long‐term stability under daylight conditions, thus allowing its storage without special precautions. In addition, two water‐soluble PEG‐based drug‐carrier molecules (mPEG2000‐oHC‐benzhydrol/phenol) are synthesized and used for drug delivery studies, monitoring the process by UV–vis spectroscopy in an ON/OFF intermittent manner. Coumarins can be rapidly synthesized from trans‐ortho‐hydroxycinnamates under visible light irradiation in the absence of a photocatalyst based on a bathochromic shift of its absorption from the UV to the visible light region under basic conditions. This methodology is applied for the preparation of dual pH‐ and photo‐responsive polymers with potential for degradable polymer and drug delivery applications.